Rancang Bangun Aplikasi Inventory Busana Muslimah Berbasis QR Code Menggunakan Flutter dan Firebase pada Butik Alsakina - Delia Pebrianti; Imam Maruf Nugroho; Yudhi Raymond Ramadhan (Jurnal ICT: Information Communication & Technology, 2026)
Alsakina Boutique is a retail business engaged in selling Muslim women's fashion such as abayas, hijabs, and prayer dresses that has been operating since 2016. As the number of products and variations in models, sizes, and colors increases, inventory management at this boutique is still carried out manually, leading to various problems such as recording errors (human error), delayed data updates, and difficulties in tracking stock in real-time. This condition results in discrepancies between recorded stock data and actual conditions in the field, which can lead to either overstock or stockout situations. This research aims to design and develop a QR Code-based inventory application for Alsakina Boutique to improve the accuracy, speed, and ease of stock recording and monitoring processes. The software development method used is Extreme Programming (XP), which consists of four stages: planning, design, coding, and testing. System design was carried out using the Unified Modeling Language (UML) approach, including use case diagrams, activity diagrams, sequence diagrams, and class diagrams. The application was developed for the Android platform using the Dart programming language with the Flutter framework, and Firebase as the database. System testing was conducted using the Continuous Integration and Continuous Deployment (CI/CD) method through GitHub Actions, covering source code checkout, dependency installation, flutter analyze, flutter test, APK build, and artifact deployment processes. The test results show that all pipeline stages were successfully executed with a success status. The resulting application provides features for managing item data, scanning QR Codes for recording incoming and outgoing items, automatic stock updates, stock change history, and real-time inventory reporting, thereby improving the efficiency and accuracy of inventory management at Alsakina Boutique compared to the previous manual system.